HDAC6 facilitates LUAD progression by inducing EMT and enhancing macrophage polarization towards the M2 phenotype - Yantao Jiang; Ju Zhang; Junjie Yu; Wei Luo; Qingwu Du; Wenting Liu; Qi Xu; Xueyang Li; Huiyan Liu; Dingzhi Huang; Tingting Qin (npj Precision Oncology)
Abstract Histone deacetylase 6 (HDAC6) plays a critical role in lung adenocarcinoma (LUAD) prognosis and the tumor immune microenvironment (TIME). This study, utilizing public datasets and experimental validation, revealed that HDAC6 is upregulated in LUAD, correlating with poor survival outcomes and an immunosuppressive TIME characterized by increased Tregs, CAFs, M2 macrophages, and MDSCs. HDAC6-high patients showed reduced immunotherapy response. HDAC6 knockout inhibited tumor growth, suppressed PI3K/AKT/mTOR signaling and EMT, and enhanced apoptosis and M1 macrophage recruitment. HDAC6 inhibition synergized with anti-PD-1 therapy, suggesting a potential combinatorial strategy for LUAD treatment. HDAC6 serves as a key prognostic marker and therapeutic target in LUAD.